Emocionalización de la justicia de menores: un análisis preliminar = Emotions in Juvenile Justice : a preliminary analysis - Bernuz Beneitez, María José (Política criminal, 2021)
Juvenile justice intervenes when juveniles commits crimes with the main objective of holding responsible for the acts committed, promoting their social reintegration and avoiding the consolidation of criminal careers. The reasons for the intervention, the conditions in which it is carried out, its educational purpose, or the fact that the judge is an adult and the court is a minor favors that, sometimes, the task of judging turns into a moral evaluation of the juvenile through his external behavior and the externalization of his feelings and emotions regarding the crime and his/her victim. In this paper we are interested in focusing on this emotional dimension of the task of judging, specially on the procedural moments that may be suitable to glimpse the emotions of minors with regard to the crime committed and the harm caused. It is something that can reorient the judicial measure or allow resolve the case in a restorative manner. This preliminary analysis, through a bibliographical review, may allow us to think about the distance, or not, between moralizing the minor and making the person responsible for the crime committed.